Analisis Pengaruh Harga, Produk, Dan Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada PT. Jalur Nugraha Ekakurir (JNE) Tebing Tinggi - Prakoso, Dandy; Polewangi, Yudi Daeng; Prasetyo, Healthy Aldriani (Universitas Medan Area, 2023)
The study analyzed the effect of price, product, and service quality on customer satisfaction at PT. Jalur Nugraha Ekakurir (JNE) Tebing Tinggi. This research was a quantitative descriptive study with data analysis techniques used, namely multiple linear regression and hypothesis testing (t-test and f test). This research was conducted at PT. Jalur Nugraha Ekakurir (JNE) Tebing Tinggi. On Gen. Sudirman street No.397 Medan-Tebing Tinggi, it was held on 12 December 2020 to 12 February 2021. The data collection method used a questionnaire and documentation. The results of multiple linear regression analysis obtained Y=6.226+0.085X1+0.244X2+0.184X3+e. The results showed that the Price had no positive and significant effect on Consumer Satisfaction at PT. JNE Tebing Tinggi indicated by the value of t count (0.873) t table (1.984) meaning that the Price had no significant effect on Consumer Satisfaction, so H1 was rejected. The product had no positive and significant effect on Consumer Satisfaction as indicated by the t value (1.975) 1 table (1.984), meaning that the product had no significant effect on Consumer Satisfaction, so H2 was rejected. Service Quality had a positive and significant effect on Consumer Satisfaction as indicated by the value of t count (3.477) t table (1.984), meaning that Service Quality had a significant effect on Consumer Satisfaction, so H3 was accepted. Price, Product, and Service Quality together had a positive and significant effect on Consumer Satisfaction. This was indicated by the value of Fcount (13.559) Ftable (3.09) meaning that the variables of price, product, and service quality together had a positive and significant effect on Customer Satisfaction at PT. JNE Tebing Tinggi then H4 was accepted. The coefficient of determination (R square) was 0.298, which meant 29.8% of the Consumer Satisfaction variable could be explained by the three independent variables consisting of Price, Product, and Service Quality, while the remaining 70.2% of the Consumer Satisfaction variable was influenced by other variables not discussed in this research.